The Effect of Growth Hormone on Growth of Cyprinus carpio (L. 1758) and Tilapia zillii (Gervais, 1848) and their Muscles - Abdulsamad, Saad M. Saleh; . Mansour, Akeil J; Yesser, Abdulkareem T. (Iraqi Journal of Aquaculture, 2016)
The present study investigate the effect of injections of Recombinant Human Growth Hormone (by LG® Life Sciences) on growth indicators of common carp Cyprinus carpio (L. 1758) and red belly tilapia Tilapia zillii (Gervais, 1848) and their muscles by injection of this hormone intraperitoneally (IP) with three replicates for two doses low and high, with 60 and 120 μg of human growth hormone/g Body weight respectively for both species, along with a control of 120 μg of normal saline/g Body weight. Then the changes were followed up in each treatment after every two weeks to pursue histological changes in the muscular tissue by using Cell Profiler software and measuring of growth indicators (specific growth rate (SGR) and condition factor (Kn)). The results of the study revealed that the maximum rate of percentages of the muscle fibers with area less than 314 μm2 for region R1(Dorsal side) was 88.29% in carp in high dose treatment after the eighth week of injection, while it was 88.00% for tilapia in high dose treatment after the eighth week of injection, too. In the region R2 (in tail) the maximum rate of percentages of muscle fibers with area less than 314 μm2 was recorded after the eighth week from the beginning of injection was 73.3553% for carp in high dose treatment and 85.935% for tilapia in high dose treatment. The results showed that 1.00984 and 1.000074 were the highest and the lowest values of condition factor for carp respectively. For tilapia those were 1.009993 and 1.000151 the highest and the lowest values of it respectively. The rate of specific growth rate for length was 0.3616 and 0.44866 cm/day% for carp and tilapia respectively. While the specific growth rates for weight were higher than the comparable one for length and were 1.3489 g/day% for carp and 1.6085 g/day% for tilapia.